Interactive programmes on private radio stations in Ghana: An avenue for impoliteness - Thompson, R.A.; Anderson, J.A. (Journal of African Media Studies, 2018)
This study aims at showing the impoliteness strategies employed during some radio interactions. The data used here are mainly recordings of the morning shows of some private radio stations in Ghana. We establish that all the recorded utterances have some features that correspond with at least one of Culpeper’s (1996, 2005) impoliteness strategies, which are bald on record impoliteness, positive impoliteness, negative impoliteness, off-record impoliteness and withhold politeness. However, many of the participants prefer the use of the on-record strategies to the off-record strategies of impoliteness. We therefore assert that many participants in interactive radio programmes in Ghana prefer to convey messages to their addressees in a more direct and unrestrained manner, with little or no attention to their (addressees’) face needs. These participants attack the faces of more powerful people not only to demean their social status but also to demand quicker results and gain some psychological relief.